Falls and comorbidity: The pathway to fractures. Issue 3 (May 2014) - Jørgensen, Terese Sara Høj; Hansen, Annette Højmann; Sahlberg, Marie; Gislason, Gunnar H.; Torp-Pedersen, Christian; Andersson, Charlotte; Holm, Ellen
Aims: To compare nationwide time trends and mortality in hip and proximal humeral fractures; to explore associations between incidences of falls risk related comorbidities (FRICs) and incidence of fractures. Methods: The study is a retrospective cohort study using nationwide Danish administrative registries from 2000 through 2009. Individuals aged 65 years or older who experienced a hip or a proximal humeral fracture were included. Incidence of hip and of proximal humeral fractures, incidence of FRICs (ischemic heart disease, COPD, dementia, depression, diabetes, heart failure, osteoporosis, Parkinson's disease and stroke) and incidence rate ratios (IRR) for fractures in patients with FRICs, and all-cause mortality up to 10 years after a hip or a proximal humeral fracture were analysed. Results: A total of 89, 150 patients experienced hip fractures and 48, 581 proximal humeral fractures. From 2000 through 2009, the incidence of hip fractures per 100, 000 individuals declined by 198 (787 to 589, OR = 0.75, CI: 0.72–0.80) among males and by 483 (1758 to 1275, OR = 0.74, CI: 0.72–0.77) among females. Incidences of FRICs decreased. The absolute reduction in fractures was most pronounced for the age group above 75 years (2393 to 1884, OR = 0.81, CI: 0.78–0.83), but the relative reduction was more pronounced in the age group of 65–75 years old (496 to 342, OR = 0.70, CI: 0.66–0.74). IRRs for hip fractures and for proximal humeral fractures were significantly elevated in patients with FRICs. Conclusions: The results suggest that the overall reduction in fractures can be explained by reduction in falls related comorbidity.